Faktor – Faktor Yang Berhubungan Dengan Pelaksanaan Skrining Pranikah Pada Calon Pengantin Perempuan Di Puskesmas Kecamatan Pancoran Jakarta Selatan Tahun 2024 - Putri Amalia; Wiwin Nur Fitriani; Eka Bati Widyaningsih (Akademi Kebidanan Bunga Husada Samarinda, 2025)
Background : premarital screening is a medical examination that will be carried out by health officials such as midwives on prospective brides before marriage to prepare for a healthy and planned pregnancy. According to data from the World Health Organization (WHO) in 2023, there are an estimated 12.7 million births among teenage girls aged 15-19, and nearly half a million births among very young girls aged 10-14, all of which represent 10% of all births worldwide. Based on preliminary studies conducted by researchers, data on visits by prospective brides at the Pancoran Sub-District Health Center in 2021 were 976 prospective female brides who conducted pre-wedding screening, in 2022 there was a slight decrease in visits by 928 prospective brides and in 2023 the number of visits by prospective female brides was 848 people, based on the latest data obtained by researchers bride visits until June 2024 were 397 people. Objective : to determine the factors related to the implementation of premarital screening on prospective brides in the Puskesmas area of Pancoran District, South Jakarta in 2024. Methodology : type of survey research with descriptive and analytical research sample this study is a Purposive sampling technique as many as 200 respondents. Analysis using Chi-square. Result : the result obtained from The Chi-square. age (p-value 0.590), occupation (p-value 0.030), knowledge (p-value 0.036), attitude (p-value 0.026). Conclusion : there is no relationship between age and the implementation of premarital screening. there is a relationship of employment, knowledge, and attitudes towards the implementation of premarital screening. Suggestion : in couples prospective brides be positive, seek information about pre-wedding screening to increase knowledge of prospective brides, and can take the time to carry out pre-wedding screening at least 6 months before marriage.